Management of infusion reactions to systemic anticancer therapy: ESMO Clinical Practice Guidelines - Roselló, Susana; Jordan, Karin (Annals of oncology, 2017)
Most anticancer treatments carry a risk for infusion reactions (IRs); incidence may increase when different agents are administered concomitantly. IRs are either allergic reactions to foreign proteins [generally immunoglobulin E (IgE)-mediated allergic responses] or non-immune-mediated reactions. Most IRs are mild with symptoms such as chills, fever, nausea, headache, skin rash, pruritus, etc. Severe reactions are less frequent and may be fatal without appropriate intervention. It is difficult to evaluate these reactions through prospective randomised studies because of the unexpected nature of these events. There is a lack of consensus in the terminology or grading of the severity of an IR in the medical literature.